Conspiracy Theories: A Public Health Concern and How to Address It - Leonard, Marie-Jeanne; Philippe, Frederick L. (Frontiers in Psychology, 2021)
The SARS-CoV-2 pandemic was characterized by a significant increase in the endorsement of conspiracy theories. Conspiracy theories are narratives that can enable and accentuate distrust towards health professionals and authorities. As such, they can lead to violent radicalization and should be considered as a public health issue. This Perspective article aims to further professionals’ understanding of conspiracy theories via the 3N model of radicalization and self-determination theory. Based on empirical research, theory, and existing interventions, potential initiatives intended to tackle the issue of conspiracy theories during pandemics are also presented.